RESPON BIBIT KELAPA SAWIT YANG TERSERANG Ganoderma sp. TERHADAP APLIKASI PUPUK KALIUM DAN Bacillus sp. ENDOFIT - Nurul Huda Sholikhatul Khusna; Fifi Puspita; Nelvia Nelvia (UIR Press, 2016)
This study aims to determine the effect of Endophytes Bacillus sp. and potassium (K), and get the best combination in inducing stem rot disease and growth of oil palm seedlings. This research was conducted at BioCertilizer and Biopesticide Industrial Unit (BICCOM) of Riau University with experimentally using Factorial Randomized Design (RAL) with two factors, 3 replications. The first factor was the concentration of Endophytes Bacillus sp., B1 (3,37x1011 cfu/ml), B2 (2,98x1012 cfu/ml), B3 (2.79x1013 cfu/ml). The second factor was the K dose, consisting of 4 levels: K0 (without K), K1 (0.1 g/polybag), K2 (0.25 g/polybag), K3 (0.5 g/polybag). The data obtained were analyzed statistically with anova and DMRT 5%. The parameters observed were incidence of symptoms, disease intensity, salicylic acid concentration, seed height, leaf number, base diameter, root shoot ratio and seedlings dry weight. The results indicate that Endophytes Bacillus sp. and K fertilizer and single factor K fertilizer did not affect all parameters. Single factor Endophytes Bacillus sp. are able to inhibit the emergence of early symptoms, reduce disease intensity, salicylic acid concentration, seed height, number of leaves, stem diameter and dry weight of seedlings. Combination of Endophytes Bacillus sp. 3.37x1011 cfu/ml and K 0.25 g/polybag tend to increase the number of leaves, stem diameter and dry weight of seedlings.